A study of potential calibrators using the KAT-7 radio telescope - Kassaye, Ermias Abebe (Department of Mathematics and Applied Mathematics, 2015)
This thesis presents a study of potential calibrators observed by the Karoo Array Telescope (KAT-7). The KAT-7 is an engineering prototype for the coming sensitive array, the MeerKAT, one of the pathfinders for the Square Kilometre Array (SKA). This thesis plays a supporting role in the ongoing commissioning activities of the KAT-7, whose construction started in early 2008, and which has been undergoing engineering and science verifications since late 2010. This thesis has achieved the first steps towards identifying possible flux-density standards for short baseline interferometers such as the KAT-7. The systematic error for flux-density calibration at KAT-7 was estimated relative to 3C123, and it was found to be ~5% of the measured flux density. 18 (~47%) of the 38 sources were identified as good flux density calibrator candidates, for their Modulation Index (MI) and Variability Index (VI) values were less than 0.05 and all the sources in the field had less than 10% of the peak flux density of the calibrator candidate. One source (PKS J0837-1951), which showed low variability and hence appeared to be a good flux-density calibrator candidate (class A), was deemed to be not a good flux-density calibrator candidate because a strong confusing source was found within its primary beam. Eight sources had MI or VI values between 0.05 and 0.09 and may deserve further study as potential flux calibrator candidates. Five sources had MI or VI values greater than 0.09 suggesting significant variability while 17 sources had only one or two observations so their suitability as potential flux calibrator candidates could not be evaluated. In addition, we used another measure of variability, the de-biased modulation index, for our sources comparing the observed modulation indices against Monte Carlo simulations. The result showed that the values of Md are largely as expected and the uncertainties therefore not substantially underestimated.